Economic Impact of Software Patching and Optimal Release Scheduling. (13th April 2016) - Anand, Adarsh; Agarwal, Mohini; Tamura, Yoshinobu; Yamada, Shigeru
Abstract : Because of highly distributed nature of software products, the task of improving software reliability is becoming a complex job. Specialized tools and techniques are being used to isolate the risky software modules. In order to retain in market, firms are required not only to provide the software on time but also to endow with continuous processing. Product updating is the process that comes to safeguard the firm's image at this point of time. And one such attribute of updating is providing software patches. Today, almost all software firms are providing either patching, module exchange or service pack application processes consequent to a release. This paper proposes a scheduling policy for a software product and shows the importance of patching in lowering the system outages and making the system more cost effective. Validation on the proposed policy has been done using real life software failure data set of Tandem Computers. Copyright © 2016 John Wiley & Sons, Ltd.